Disaffected : the cultural politics of unfeeling in nineteenth-century America - Yao, Xine, 1985- (Perverse modernities., 2021)
"Xine Yao explores the racial and sexual politics of unfeeling--affects such as coldness, insensitivity and sexual frigidity that are not recognized as feeling--as a means of survival and refusal for people of color and queer people in nineteenth-century America."--